Dual-Responsive Methotrexate-Human Serum Albumin Complex-Encapsulated Liposomes for Targeted and Enhanced Atherosclerosis Therapy - Wang X; Chen X; Ji H; Han A; Wu C; Jiang J; Nie Y; Li C; Zhou X (International Journal of Nanomedicine, 2025)
Xueqin Wang,1,* Xiaodong Chen,1,* Huawen Ji,1,* Along Han,2 Chengxi Wu,1 Jun Jiang,1 Yu Nie,3 Chunhong Li,4 Xiangyu Zhou1 1Department of Thyroid Surgery, Affiliated Hospital, Southwest Medical University, Luzhou, People’s Republic of China; 2Beijing Advanced Innovation Center for Soft Matter Science and Engineering, State Key Laboratory of Organic‒Inorganic Composites, State Key Laboratory of Chemical Resource Engineering, Beijing Laboratory of Biomedical Materials, Bionanomaterials & Translational Engineering Laboratory, Beijing Key Laboratory of Bioprocess, Beijing University of Chemical Technology, Beijing, People’s Republic of China; 3National Engineering Research Center for Biomaterials, Sichuan University, Chengdu, People’s Republic of China; 4Department of Pharmaceutical Sciences, School of Pharmacy, Southwest Medical University, Luzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chunhong Li, Email lispringhong@126.com; Xiangyu Zhou, Email xiangyuzhou971@vip.126.comIntroduction: In plaque sites of atherosclerosis (AS), the physiological barrier caused by the thick fiber cap due to the overmigration of vascular smooth muscle cells (VSMCs) prevents efficient drug delivery to damaged macrophages. How to ensure precise targeted delivery of drugs to plaque sites and their on-demand release to dysfunctional cells under the thick fibrous cap are feasible solutions to enhance AS treatment.Methods: A small complex of methotrexate (MTX)-human serum albumin (HSA) with strong, thick fibrous cap penetration ability was encapsulated in a cholesterol hemisuccinate (CHEM) prepared pH-sensitive liposome, modifying with ROS-responsive PEG2000-TK-DSPE (PTD), termed PTD/Lipo/MTX-HSA.Results: PTD/Lipo/MTX-HSA can achieve precise targeting and on-demand release in response to plaques environments of AS. The designed formulation accelerated the release of the small-sized MTX-HSA complex in response to excess ROS and acidic pH conditions, and it better penetrated the macrophage spheroids. Furthermore, it has precise targeting ability in the AS mouse model and can produce good anti-inflammatory efficacy by inhibiting p65 entry into the nucleus turn out inflammatory factor.Conclusion: Our formulations work with safety in mind, and it also highlights the potential of precisely targeted and on-demand-released dual-responsive smart nanoplatforms as promising therapeutic options to penetrate deeper plaques for the effective treatment of AS.Keywords: methotrexate-human serum albumin complex, dual-responsive smart liposomes, penetration of deeper plaques